Secular trends and related factors in leisure-time sedentary behavior among Koreans: an analysis of data from the 2011-2017 Korea Community Health Survey - Hyun-Ju Seo; Min-Jung Choi; Soon-Ki Ahn (Epidemiology and Health, 2022)
OBJECTIVES Sedentary behavior has gradually increased and has become a public health problem. Therefore, this study investigated trends in weekday leisure-time sedentary behaviors, as well as characteristic socio-demographic and lifestyle correlates in Korean adults. METHODS We analyzed data from 914,946 adults aged ≥19 years who participated in the Korea Community Health Survey (2011, 2013, 2015, and 2017). Leisure-time sedentary behavior was categorized as a binary variable (<4 and ≥4 hr/day). Multivariable regression analysis was used to model the prevalence of sedentary behavior and estimate odds ratios. RESULTS The prevalence of leisure-time sedentary behavior decreased from 15.2% to 14.4% in men and from 16.6% to 16.0% in women between 2011 and 2017, respectively. However, a significant increase was observed in subjects with an education lower than high school in both genders (β coefficient=0.12 for men and 0.08 for women, p for trend <0.001). Women in the lowest household income level (β coefficient=0.08, p for trend=0.001) and with poor subjective health status (β coefficient=0.05, p for trend=0.013) showed an increasing trend. Other factors associated with sedentary behavior were age, education level, body mass index, household income, walking activity, perceived stress level, and subjective health status in both genders. CONCLUSIONS Identifying the secular trends and correlates of sedentary behavior by gender and associated factors will provide empirical evidence for developing public health campaigns and promotion programs to reduce sedentary behavior in Koreans.